Fostering Inclusivity: Strategies for Supporting Students with Special Needs in Mainstream Classrooms - Hasanah, Rizkiyah; Agus R, Abu Hasan; Munawwaroh, Izzatul; Nisa’, Khoirun; Hasanah, Maulidatul; Mundiri, Akmal (UAS PRESS, 2024)
This research analyzes encouraging inclusivity: strategies for supporting students with special needs in general classes. This research uses a qualitative case study approach. The research subjects comprised the Head of the Madrasah, the Deputy Head of Student Affairs, the Deputy Head of Curriculum, the Deputy Head of Infrastructure, and Guidance and Counseling for Teachers, Students, and Parents. Data collection techniques use interview observation and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The research results show that implementing an inclusive approach in general classes requires an integrated combination of methods and techniques. First, intensive teacher training is vital, focusing on improving skills in identifying and responding to individual student needs. Furthermore, developing flexible and adaptive teaching materials allows students with special needs to access the curriculum in a way that suits their abilities. Educational technology, such as software that supports differentiated learning and communication tools, also plays an important role. Emotional and social support, through counselling programs and the formation of peer support groups, contributes to creating an inclusive and supportive environment. The results of this research underscore the importance of collaboration between teachers, parents, and communities in creating a supportive educational ecosystem for all students, especially those with special needs.